Simulation tools for a smart grid and energy management for microgrid with wind power using multi-agent system. Issue 6 (December 2020) - Azeroual, Mohamed; Lamhamdi, Tijani; El Moussaoui, Hassan; El Markhi, Hassane
The smart grid concept is predicated upon the pervasive use of advanced digital communication, information techniques, and artificial intelligence for the current power system to be more characteristics on the real-time monitoring and controlling of the supply/demand. Therefore, in recent years, researchers increasingly couple distinct simulators to form novel "co-simulations." In this article, we will present a survey of different electrical power and communication simulators, a literature survey of 20 smart grid co-simulations frameworks, and the characteristics of each platform applicable in the intelligent electrical network. Finally, we proposed multi-agent systems for controlling the microgrid that consists of wind power and storage system using MACSimJX co-simulation that combines Simulink simulator and JADE (Java Agent Development Environment).